Latent inhibition in humans: data, theory, and implications for schizophrenia. - Lubow, R. E.; Gewirtz, Jonathan C. (Psychological Bulletin, 1995)
Learning about the consequences of a stimulus is retarded if that stimulus has been experienced without reinforcement. A literature review of this latent inhibition (LI) effect indicates that LI is similar in human and other species, although in adult humans it often requires a masking or distracter task. The discrepancy in conditions for producing LI can be accounted for by developmental differences in the automatic processing of unattended stimuli. In adults, automatic processes are subject to a controlled information-processing override. Masking prevents controlled processing of the preexposed stimuli so that they remain unattended. The role of masking in attenuating LI in schizotypal/schizophrenic groups is assessed. It is proposed that schizophrenia is related to an inability to use occasion-setting properties of context or to switch from controlled to automatic processing of inconsequential events. Reprinted by permission of the publisher.